The Influences of Environmental Performance and Green Innovation on Firm Value with Mediated Financial Performance - Da'i, Lilik Wahyudin 'Amil; Yuliana, Indah (Jurnal Ecogen, 2025)
The main purpose of this study is to determine and examine the influences of environmental performance and green innovation on firm value with mediation of financial performance. The object and focus of this research are non-financial companies listed on the IDX for the 2021-2023 period with a population of 649 companies. The sample was selected based on purposive sampling technique with a total of 79 companies that met the criteria. The data was analysed using the SEM-PLS method. The results revealed that environmental performance does not have a significant effect on firm value. Green innovation and financial performance have a significant positive effect on firm value. Environmental performance and green innovation significantly and positively influence financial performance. Furthermore, financial performance is proven to mediate the effect of environmental performance and green innovation on firm value.